Response of the citrus rootstock genotypes against artificial inoculation of Phytophthora nicotianae - SINGH, KULDEEP; SHARMA, R M; DUBEY, A K; KAMIL, DEEBA; S, LEKSHMY; AWASTHI, O P; JHA, G K (The Indian Journal of Agricultural Sciences, 2018)
Effect of Phytophthora nicotianae Breda de Haan pathogen on different rootstock genotypes including sour orange, Troyer citrange and six variants of C. jambhiri Lush, viz. RLC-5, RLC-6, RLC-7, Grambhiri, rough lemon and Italian rough lemon were studied. Of the various rootstocks, Phytophthora inoculation tended to show significantly maximum plant height in Grambhiri (30.45cm). Significantly highest leaf numbers/plant (30.45), fresh root mass (4.13g) and dry root mass (2.47g) were recorded in the infected plants of RLC-5, however, it was statistically similar with sour orange, Italian rough lemon and Troyer citrange for leaf numbers, RLC-6 and Grambhiri for fresh root mass and RLC-6 and Italian rough lemon for stem diameter. RLC-6 had the highest stem diameter (3.62 cm) without having significant difference with RLC-5, RLC-7 and Italian rough lemon. After fungal inoculation, Troyer citrange showed the highest feeder root volume (2.45 cm3) followed by sour orange. These two rootstocks also prove superiority to have the highest photosynthetic rate (A) and transpiration rate (E) over other infected genotypes of citrus rootstocks tested. Except Italian rough lemon and rough lemon, all the rootstocks were found similar statistically in respect of stomatal conductance (gs). Overall,Troyer citrange proved best, and showed the lowest reduction in growth and physiological attributes after fungal inoculation. Being a Phytophthora tolerant rootstock, Troyer citrange was considered the standard rootstock to study the per cent change in disease incidence and feeder root infection in other genotypes, which indicated sour orange to be the next best rootstock. Of the six variants of Italian rough lemon, RLC-5 and RLC-6 tended to show the lower root infection than rest of the variants studied.